POTENSI TRIATOMA SP DALAM PENYEBARAN PENYAKIT TULAR VEKTOR EMERGING DI INDONESIA - Risqa Novita (Vektora : Jurnal Vektor dan Reservoir Penyakit, 2019)
The era of globalization allows migration fastly, so we do not have boundary of a country. This led to an increase of the infectious diseases. Indonesia also have an impact on this globalization by highly migration. Indonesia is a tropical country and has diversity of vectors that can transmit various tropical diseases. One of a vector which transmitted vector borne diseases is a bug Triatoma. Triatoma lives near the people’s house and in the bed. One of the species of Triatoma which found in indonesia is Triatoma rubrifasciata which is vector of Chagas disease and Leprosy and can cause allergic reaction of the skin after the bite. Triatoma infection in Southeast Asia, including in Indonesia has not been widely reported. This condition should make us to be alert on the disease emerging or re emerging diseases that can be caused by Triatoma . This article aims to study Triatoma as a vector of emerging and potentially re emerging diseases in Indonesia, which are Chagas, skin allergic reaction after bite and Leprosy. Methods. Literature review by look in google scholar and pubmed, by search using keywords: emerging parasitic, vector borne diseases, Triatoma in Southeast Asia. Inclusion criterias are research articles, laboratory research, case report, and systematic surveillance. Based on the literatures, tracing data that Indonesia has a chance to be the cases of Chagas disease, Skin allergic reaction of Triatoma and Leprosy. It is supposed to made the vigilance on make a early warning system, so our public health coud be achieved highest.